Evaluation of hepatoprotective effect of methanolic extract of Clitoria ternatea (Linn.) flower against acetaminophen-induced liver damage - Nithianantham, Kuppan; Kwan, Yuet Ping; Yoga Latha, Lachimanan; L. Jothy, Subramanion; Ibrahim, Darah; Yeng, Chen; Chew, Ai Lan; Sasidharan, Sreenivasan (Elsevier, 2013)
Objective To evaluate the hepatoprotective and antioxidant activity of Clitoria ternatea (C. ternatea) flower extract against acetaminophen-induced liver toxicity.